Empedocles Arbiter Symposii: Luxury, Political Equality, and Bizarre Dinner Parties in Fifth-Century Acragas - Andolfi, Ilaria (Histos, 2020)
This paper analyses Empedocles’ contribution to Sicilian politics as described by the ancient sources cited by Diogenes Laertius. It offers a close analysis of a bizarre anecdote by Timaeus (FGrHist 566 F 134), where Empedocles got rid of a potential tyrant to preserve political equality, also in the light of other ancient accounts in which Empedocles is described as a man of his people.